Pengaruh Tanggapan Siswa Tentang Pengelolaan Kelas Dan Motivasi Belajar Terhadap Kedisiplinan Siswa Kelas V SD Negeri Kedungwaduk 1 Karangmalang Sragen Tahun Ajaran 2015/2016 - Sulistyoningsih, Esti Nur, Drs. Saring Marsudi, SH. M.Pd (2016)
Education can be obtained anywhere, anytime and with anyone. One of the key success in education is learning. The purpose of this study was to determine include: 1) the influence of student respons on classroom management discipline within the fifth grade students of SDN Kedungwaduk 1 Sragen in the academic year 2015/2016, 2) influence the learning motivation to discipline students of class V SDN Kedungwaduk 1 Sragen in the academic year 2015/2016, 3) influence student responses on classroom management and learning motivation to discipline class fifth students at SDN Kedungwaduk 1 Sragen in the academic year 2015/2016. This type of research is based on a quantitative approach to the type of research Ex-Post Facto. Populations dan sample are V class in the SDN Kedungwaduk 1 Sragen. Used Quesioners, interview, and documentations. The analysis technique used is multiple linear regression, t test, and test f. Based on the analysis of data: 1) equation regression coefficient obtained Y = 8322 0, 585 X1 + 0, 408 X2. 2) Results of t test student respons on classroom management to discipline students tcount (5585)> ttable (2.032), student of class management positive effect on student discipline. 3) Learning motivation positive effect on student discipline, it is based on t test results tcount (3458)> ttable (2.032). 4) The test results f significance value 0.000 <0.05, significant feedback on classroom management and student motivation to learn together positive effect on student discipline fifth grade students of SDN 1 Sragen Kedungwaduk academic year 2015/2016. Keywords: Respons On Classroom Management, Learning Motivation, Discipline Students